CREATIVE THINKING : A STUDENT PROFILE ON SOLVING FRACTION PROBLEM - Ita Sari; Nailul Authary (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2022)
The aim of this study was to determine students' thinking processes in solving fractional problems. This research is expected to provide benefits in the form of information about students' thinking processes in solving fraction problems so that it can be used as a reference for educators in general in teaching fractions material. The formulation of the problem in research is how students think in solving fractional problems. Place The research was conducted at Ibnu Khaldun Junior High School, Banda Aceh. The subject of this research is one person. This study uses a qualitative approach. The results of this study are choosing a rare completion by multiplying the denominator times the denominator and the quantifier times the numerator. In solving problems with different denominators, the subject chooses to equate the denominators by multiplying the two denominators on the problem. A further creative rarity is if the question has a different denominator, that is, the denominator is different, then the subject solves the problem by means of a cross and the denominator is multiplied by the denominator, then the subject can simplify the form of the fraction by equally dividing it by one number.